Pemanfaatan Cloud Computing untuk Solusi Disaster Recovery dan Kontinuitas Bisnis Sistem Informasi Utama (Studi Kasus: Universitas Pamulang) - Chairul Anwar; Gilang Ramadhani; Muhammad Zaky Aditiya; Putri Arum Sari (PT Jurnal Cendekia Indonesia, 2025)
This study examines the use of cloud computing as a disaster recovery (DR) and business continuity (BC) solution for key information systems at Pamulang University. The university's reliance on digital systems increases its vulnerability to disruptions that could potentially lead to data loss and service disruption. The objective of this study is to formulate a strategic model for implementing effective cloud-based DR/BC, focusing on crucial systems such as the Academic Information System (SIAKAD) and the Financial Information System. The research method uses an iterative approach, involving repeated cycles of risk analysis, solution design, conceptual implementation, and simulation testing. This approach allows for gradual risk identification and mitigation, as well as adaptation to evolving needs. The implementation of cloud computing is expected to provide a scalable, flexible, and cost-effective recovery environment, ensuring rapid data availability and operations post-disaster. The results of this study will provide a practical framework for Pamulang University to strengthen the resilience of its information systems, minimize downtime, and maintain the continuity of educational services amidst potential threats.